Economic analysis of on-farm trial of drought tolerant maize in Kwara state Nigeria: a gender approach - Ayinde, O.E.; Abdoulaye, T.; Takim, F.O.; Oloyede, A.O.; Bankole, F.A. (Trakia University, 2016)
This study analyzed the profitability of on-farm trial of Drought Tolerant (DT) Maize in Kwara State Nigeria using a gendered innovation approach. A Two-stage stratified sampling technique was used. The primary data for the study were collected through the use of well-structured questionnaires administered to forty (40) women farmers in an on-farm trial of the DT maize variety. The analytical tools used include Descriptive statistics, Ranking and Farm budgeting analysis. The result of the analysis showed that the women farmers were all married with only 10% of the farmers having no formal education and of an average age of 41 years. The result of varietal preference differs in some locations. The women farmers ranked the DT maize variety as the best at two of the locations. The profitability of the maize varieties also differs per location with the DT maize varieties having the highest profit at three locations. It is therefore recommended that women farmers should be involved in the varietal selection procedure so as to facilitate easy adoption of the drought tolerant maize. This will ensure that the women farmers’ needs and preferences are incorporated in the development of agricultural innovations.